Strong poison - Sayers, Dorothy L. (Dorothy Leigh), 1893-1957. (London : New English Library : Hodder & Stoughton, 2003)
Lord Peter Wimsey defends a young detective-story writer on trial for her lover's murder and asks her to marry him when he first takes the case.
Adult.
Adult
Keywords: Private investigators -- England -- Fiction; Wimsey, Peter, Lord (Fictitious character) -- Fiction; Mystery fiction; Detective and mystery stories